Design and experiment study on the performance of liquefied natural gas cold energy recovery - Fareez Khan Mohd Hasrat (2019)
This paper investigated on the cold energy recovery process (CERS) from the regasification of cryogenic LNG. The cryogenic regasification process will produce a large amount of cold energy. The main objective of this paper is to analyse the process and theories used in CERS and regasification processes and apply the theories to design an improved heat exchanger. This paper studied an experiment which involved cryogenic liquid nitrogen (LN2) and ethylene glycol-water 50%-50% solution’s (EG) heat exchange process via a series of three heat exchangers: the evaporator, superheater and recuperator. The design of the heat exchanger was to be made with reference to the specifications of the evaporator. The dimensions of the fins, the total number of layers and the arrangement of the hot and cold layers of the heat exchanger were examined with respect to the structure of the evaporator. Thus, the dimensions and the layering arrangement of the heat exchanger were manipulated to produce a greater heat exchange area, A and Number of Transfer Units (NTU). The effectiveness of the heat exchanger was calculated based on the Ɛ-NTU method which was dependent on A and NTU. Thus, a greater A resulted in a higher value of NTU which in turn boosted the effectiveness of the heat exchanger from 93% to 96.5%. Thus, a more effective heat exchanger can enhance the performance of the CERS.